Lithiophilic V2CTx/MoO3 Hosts with Electronic/Ionic Dual Conductive Gradients for Ultrahigh‐Rate Lithium Metal Anodes - Yao, Wei; Chen, Zhiwei; Zhang, Xiao; Luo, Juhua; Wang, Jinshan; He, Meng; Chen, Chi; Cheng, Xin‐Bing; Xu, Jianguang (Advanced functional materials, 2024)
Lithium (Li) metal is considered as a promising anode material for high‐energy batteries; yet, its practical application is hindered by uncontrolled Li dendrite growth, especially at a high rate. Herein, a dual conductive gradient V2CTx/MoO3 (DG‐V2CTx/MoO3) host that integrates electronic/ionic conductive gradients and lithiophilicity is prepared by layer‐by‐layer assembly for dendrite‐free Li anodes. Gradient LiF deriving from different amount of V2CTx endows a good ionic conductive gradient; while, MoO3 is regarded as a spacer to avoid the restacking of V2CTx, increasing space for Li deposition. The dual conductive gradients effectively optimize the current density and Li+ flux distribution at the bottom, achieving fast reduction of Li+ and a “bottom–up” Li deposition mode. Meanwhile, the lithiophilic V2CTx and MoO3 guide the homogeneous Li growth. As a result, the symmetrical half‐cells based on DG‐V2CTx/MoO3@Li anodes conduct 700 h at 5 mAh cm−2 and 20 mA cm−2. The DG‐V2CTx/MoO3@Li||LiFePO4 full‐cells maintain a capacity retention of 85.4% after 1350 cycles at 2 C. Remarkably, the DG‐V2CTx/MoO3@Li||LiNi0.6Co0.2Mn0.2O2 full‐cells can run 150 cycles with 80.6% capacity retention even at harsh conditions. The well‐adjusted materials and structures with both dual conductive gradients and lithiophilic properties will bring inspiration for novel material design of other metal batteries. The electronic/ionic dual conductive gradients of the DG‐V2CTx/MoO3 promote the uniform distribution of the current density and Li+ flux at the bottom of the anodes, enabling preferential reduction of Li+ at the bottom layer and achieving “bottom–up” deposition mode; while, lithiophilic V2CTx and MoO3 can induce the uniform nucleation and growth of Li at high rate.